2001
DOI: 10.1198/016214501753382345
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Identification Using Projections

Abstract: This artiele describes a procedure to identify elusters in multivariate data using information obtained from the univariate proj~ctions of the sample data onto certain directions. The directions are chosen as those that minimize and maXlmlze the kurtOSlS coefficlent of the projected data. It is shown that, under certain conditions, these directions provide the largest separatlOn for the dlfferent clusters. The projected univariate data are used to group the observations according to the values of the gaps or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 36 publications
(31 reference statements)
1
78
0
4
Order By: Relevance
“…This elegant idea, first proposed by Cardoso and Soumouliac (1993), and described in detail in Oja et al (2001), is to replace the maximal variation directions of PCA with maximally non-Gaussian directions. See Peña and Prieto (2001) for a related idea. Such directions can be very useful for data visualization because they can focus on clusters, and other interesting aspects of the dataset.…”
Section: Data Objects In Image Analysismentioning
confidence: 99%
“…This elegant idea, first proposed by Cardoso and Soumouliac (1993), and described in detail in Oja et al (2001), is to replace the maximal variation directions of PCA with maximally non-Gaussian directions. See Peña and Prieto (2001) for a related idea. Such directions can be very useful for data visualization because they can focus on clusters, and other interesting aspects of the dataset.…”
Section: Data Objects In Image Analysismentioning
confidence: 99%
“…A great deal of research in the PP community has been centered on the construction of meaningful PP indexes for different purposes. It is possible to find PP indexes for clustering analysis [42,19,38,39,43,30,13], for supervised analysis [44,45,21,5] and for regression analysis [46,47]. Given that this paper is targeted to supervised analysis, we briefly describe some relevant supervised PP indexes included in the experimental evaluation of the paper.…”
Section: Projection Pursuit Indicesmentioning
confidence: 99%
“…A key advantage of PP is its flexibility to fit different pattern recognition tasks, depending on the PP index used. For example, PP can be used to perform clustering analysis [19,20], classification [21][22][23][24], regression analysis [25] and density estimation [26] (some reviews of PP indexes can be found in [21,27,28]). Another advantage of PP is its out-of-sample mapping capability, that is, the possibility to map new examples in the projection space after the construction of it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cluster analysis (or un-supervised classification) we look for a partition of the space into homogeneous groups or clusters (with small dispersion within groups), that help us to understand the structure of the data. Several cluster methods have been proposed, such as hierarchical clustering (Hartigan, 1975), k-means (MacQueen, 1967, kmediods (Kaufman and Rousseeuw, 1987), kurtosis based clustering (Peña and Prieto, 2001). From most of them we get a partition of the space in disjoint subsets.…”
Section: Introductionmentioning
confidence: 99%